Potentialities in the performance of coating mortars through the addition of sewage sludge ash (Research, Society and Development, 2021)
Through environmental policies that provide a gradual discussion about the destination of the tailings produced in the most diverse industrial sectors, the sewage sludge is emphasized by the problematic destination arising from the amount of toxic compounds that compose it, compromising its disposal. Aiming to fulfill the sustainable role through the creation of mechanisms that favor the ecological coexistence between environment and human beings, it is possible through the use of construction materials, considered as conventional, the use of calcined sewage sludge as an enhancer of the properties of matrix materials cement, significantly improving its performance against mechanical stresses and degradation mechanisms. Based on the need to implement measures to mitigate environmental impacts through the production of eco-efficient materials, the ashes of sanitary sewage sludge as a partial substitute for Portland cement have now been used as an input in coating mortars. This substitution focuses on reducing the large volume of sludge generated by the Sewage Treatment Plants, as well as on the reduction in the consumption of cement, a large CO2 generator during its manufacturing process. It was observed that through the use of this calcined by-product applied in mortars, a relevant physical-mechanical performance in cementitious materials is ratified, that in comparison to the material without the use of it, better results are observed, resulting from the reactivity conferred to the sludge after the thermal degradation process, making it a pozzolana.